The code of sustainable success in fitness apps: social comparison mechanism enabled by user facilitated supports - Kuang Wu; Qi Li; Yang Liu (Frontiers in Public Health, 2025)
IntroductionIntegrating social comparison theory and social support theory, this study develops a holistic model examining how fitness app social features influence sustainable development of users. This study not only extends the influence of user facilitated support, but also explores the social comparison factors, providing unique insights into interpreting the mechanism of continuous use intention and fitness intention.MethodsThis study collects empirical data by distributing questionnaires. We use structural equation modeling to examine the relationship between fitness app social features, continuous use intention and fitness intention.ResultsThis study finds that information support, emotional support and upward comparison affect social presence and fitness interest positively, which in turn affect continuous use intention and fitness intention positively. Interestingly, downward comparison affects social presence negatively.DiscussionThese findings provide references for fitness platform practitioners to design marketing strategies and thus improve the sustainable commercial value of fitness apps. In addition, the results can be applied to promote users’ fitness motivation and thus offer sustainable health value to the society.